Design Method of Quick Return Four-bar Mechanism based on the Geometric Principle - Xu Jin; Xu Aiqun; Zhao Qian (Jixie chuandong)
As a common quick return mechanism,the plane- four- bar mechanism is widely used in engineering. In order to improve the design accuracy and efficiency of the quick return four- bar mechanism,a relatively simple method to establish a analytic equations of the quick- four- bar mechanism is proposed through the analysis of the traditional analytical method and combining the geometric principle. By using the MATLAB software,the equations can be solved quickly. By changing the parameters value of equations,the quick- return four- bar mechanism can be designed quickly and accurately.